Numerical investigation on the relationship of cavitation initiation in bileaflet mechanical heart valves (BMHVs) with the aortic root geometry and valveâs implantation rotation angle - Abbas, S.S. (Springer, 2020)
Thromboembolism remains a major concern associated with the use of BMHVs, and one of its leading causes could be cavitation, which has been reported to occur due to rapid closing of BMHV leaflets and consequent pressure drop. The aortic root geometry and the implantation rotation of BMHV significantly affect the leaflet kinematics and associated hemodynamics of BMHV and, consequently, may also initiate cavitation which has been investigated in this study. Two aortic roots, straight and bulged, were modelled, while three implantation rotation angles of BMHV were modelled, differing by 45°. ALE was employed as the FSI method, and blood was modelled as non-Newtonian. The results show that the closing velocity of one of the leaflets of a 0° rotated BMHV was 15 higher in bulged aorta as compared to straight aorta. The maximum closing velocity of fast closing leaflet was found to increase with the increasing implantation rotation of BMHV in bulged aorta, being, respectively, 8 and 19 higher for 45° and 90° rotated BMHV as compared to a 0° rotated BMHV. Consequently, it was observed that the pressure dropped below the vapour pressure for all the modelled implantation rotation angles of BMHV in bulged aorta near the leaflet tip. The maximum pressure drop across BMHV also increased with the increasing implantation rotation of BMHV in bulged aorta, being, respectively, 20 and 44 higher for 45° and 90° rotated BMHV as compared to a 0° rotated BMHV. The leaflet kinematics have been found liable to initiate cavitation. © 2019, The Brazilian Society of Mechanical Sciences and Engineering.